Distribution Analysis of Local Ice Pressures in the Indentation Test at Various Velocities - Guojun Wang; Qianjin Yue; Dayong Zhang; Yanghua Fu; Xin Peng; Rui Dong (Journal of Marine Science and Engineering, 2022)
When sea ice acts on vertical structures, there are much higher pressures in localized areas known as high-pressure zones (HPZs) than in other areas. The damage failure mode of sea ice varies with the sea ice velocity and affects the distribution of HPZs. In this study, an indentation test that drives ice sheet interaction with a vertical rigid plate (indentor) was designed, and a pressure sensor (consisting of 32 × 32 small pressure units of 100 mm2) was installed on the indentor face to measure the local ice pressure (LIP) at various velocities. The distribution of the LIPs along the ice thickness, the probability distribution of the LIPs and the distribution relationship of the LIPS in space and time were obtained from the measurement. The results show that the LIPs were mainly distributed in the middle of the sea ice, which is consistent with full-scale observations and previous research. Ductile failure of the sea ice results in a larger LIP distribution area than brittle failure at the same threshold kt (kt = σL/σcr). The probability distribution of the LIPs decreases exponentially with increasing pressure and follows a lognormal distribution. The maximum LIP appears at the peak moment of the global force when the sea ice failure mode is mainly ductile failure. However, the maximum LIP may not occur at the peak moment when the sea ice failure is mainly brittle failure and, instead can appear at any moment in the global force time history curve. The HPZ (which is larger than 7/8 times the maximum LIP) area is less than 2% of the nominal contact area at various velocities. The influence of the sea ice velocity on the spatial and temporal distribution of LIP is analyzed, and the results provide a reference for designing structures with local strength in ice regions.